2011
DOI: 10.1016/j.jbiomech.2011.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Coupling plowing of cartilage explants with gene expression in models for synovial joints

Abstract: Articular cartilage undergoes complex loading modalities generally including sliding, rolling and plowing (i.e. the compression by a condyle normally to the tissue surface under simultaneously tangential displacement, thus generating a tractional force due to tissue deformation). Although in in vivo studies it was shown that excessive plowing can lead to osteoarthritis, little quantitative experimental work on this loading modality and its mechanobiological effects is available in the literature. Therefore, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…23,31 We performed a multiple regression analysis in order to determine what mechanical parameters influenced the gene expression. As found in previous studies, we found an increase in collagen type II and aggrecan expression with dynamic loading, 12,29 suggesting an attempt by the chondrocytes to adapt the ECM in response to the dynamic loading conditions. Fibronectin was the only gene that showed a significant correlation with multiple parameters; 66% of the fibronectin regulation in our model was correlated with strain (extrinsic) and the initial effective modulus (intrinsic).…”
Section: Discussionsupporting
confidence: 87%
“…23,31 We performed a multiple regression analysis in order to determine what mechanical parameters influenced the gene expression. As found in previous studies, we found an increase in collagen type II and aggrecan expression with dynamic loading, 12,29 suggesting an attempt by the chondrocytes to adapt the ECM in response to the dynamic loading conditions. Fibronectin was the only gene that showed a significant correlation with multiple parameters; 66% of the fibronectin regulation in our model was correlated with strain (extrinsic) and the initial effective modulus (intrinsic).…”
Section: Discussionsupporting
confidence: 87%
“…That mechanical stimulus can have such an effect has been demonstrated by several studies. 47 , 48 Similarly, the expression of degradative enzymes was increased by pro-inflammatory cytokines, which further confirms that the culture conditions created for this study were similar to those found in OA. An increase of MMPs gene expression in bovine chondrocytes was also shown by Lv et al .…”
Section: Discussionsupporting
confidence: 82%
“…A previous study from our laboratory found that increasing tractional forces, induced by sliding and plowing, induced catabolic changes within the cartilage. 18 …”
Section: Introductionmentioning
confidence: 99%